Analisis Metode Pendidikan Kesehatan Berbasis Online dalam Peningkatan Pengetahuan dan Sikap Pencegahan Narkoba pada Anak Usia Remaja - Susilaningsih, Endang Zulaicha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2021)
The results of a survey by the National Narcotics Agency (BNN) in 2018 stated that the prevalence of drug abuse in students reached 4.7 percent of the total number of students in Indonesia or around 921,695 people. This requires serious attention from health practitioners and education to make prevention efforts. The programs that are being promoted include, among others, effective online health education, through cellphones, whatsapp groups and other online facilities. The purpose of the study was to analyze the effect of online-based health education on the level of knowledge and attitudes of adolescents in drug prevention. This study is a quantitative study with a quasi-experimental design using a pre-posttest design without a control group. The research sample was 30 respondents from SMPN 2 Sumberlawang, which was held in July-September 2020. Data collection was by giving a questionnaire via an online g-form. The data were tested using the Wilcoxon test. Results: there was a significant effect (p-value = 0.000 < 0.005) of providing health education interventions through whatsapp groups using voice notes and videos about drug prevention on the level of knowledge and attitudes of SMPN 2 Sumberlawang students.